2003
DOI: 10.1016/j.ecss.2003.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the biology, dynamics, and secondary production of Talorchestia brito (Amphipoda, Talitridae) in Atlantic (Portugal) and Mediterranean (Tunisia) populations

Abstract: The biology, population dynamics, and production of Talorchestia brito were studied at two sandy beaches located on the Atlantic (Portugal) and on the Mediterranean (Tunisia) coasts, respectively. The seasonal variation in abundance and the overall densities were similar in both populations. Reproduction occurred from February to September in the Atlantic, and from March to early November in the Mediterranean. The sex ratio was male biased in the Atlantic, and female biased in the Mediterranean. Based on data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 49 publications
5
9
2
Order By: Relevance
“…This correlation is in accordance with our expectations in the sense that recruitment took place with temperature increase, leading to density increase. These results are similar to those of Marques et al (2003) and Gonçalves et al (2003) for two Atlantic populations of Talitrus saltator and Talorchestia brito, respectively. As for Zouaraa, no correlation between density and environmental factors was found, mainly perhaps because of the important decrease of the population, which does not allow statistical analysis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This correlation is in accordance with our expectations in the sense that recruitment took place with temperature increase, leading to density increase. These results are similar to those of Marques et al (2003) and Gonçalves et al (2003) for two Atlantic populations of Talitrus saltator and Talorchestia brito, respectively. As for Zouaraa, no correlation between density and environmental factors was found, mainly perhaps because of the important decrease of the population, which does not allow statistical analysis.…”
Section: Discussionsupporting
confidence: 87%
“…When assessing the effect of environmental factors on these parameters at Zouaraa, only the percentage of juveniles was positively correlated with temperature, thus controlling breeding activity, and also with sediment moisture. These results confirm those of Marques et al (2003) and Gonçalves et al (2003) for Talorchestia brito, and indicate a more important sensitivity of talitrid juveniles to dehydration (shown by their correlation with sediment moisture), which induces higher concentrations closer to the high water mark (Morrit, 1987). A correlation between juvenile percentage and temperature was also established for the population at Korba.…”
Section: Discussionsupporting
confidence: 82%
“…These types of distribution have already been observed for other species of Hyalella, such as H. pleocuta, H. castroi (Castiglioni and Bond-Buckup, 2008b) and H. azteca (Saussure, 1858) (Pickard and Benke, 1996). For other amphipods, bimodal distribution also appears to be common as, for example, in Corophium multisetosum Stock, 1952(Cunha et al, 2000, Echinogammarus longisetosus Pinkster, 1973 (Guerao, 2003), Talorchestia brito Stebbing, 1891 (Gonçalves et al, 2003) and Gammarus chevreuxi Seston, 1913 (Subida et al, 2005).…”
Section: Population Dynamics Of a Freshwater Amphipodmentioning
confidence: 99%
“…comm.). Gonçalves et al (2003), demonstrated that cohorts born in the beginning of the reproductive period, i.e., in late winter (Quiaios) and spring (Quiaios and Zouaraa), reproduced in the same season, exhibiting shorter life spans and most probably not surviving the winter.…”
Section: Discussionmentioning
confidence: 99%